Case Report: Expanding the Phenotypic Spectrum of Timothy Syndrome Type 1: A Sporadic Case With a de novo CACNA1C Pathogenic Variant and Segmental Ileal Dilatation - Nugud, Ahmed A.; ELkholy, Nermeen Mahmoud; Omar, Awad Alkarim; Qazi, Abid; Tzivinikos, Christos; Chencheri, Nidheesh; Khan, Sabina; Ba'Ath, Muhammad Eyad (Frontiers in Pediatrics, 2021)
Background: Long QT syndactyly syndrome (long QT syndrome type 8), also known as Timothy Syndrome (TS) was first described in 1994 with still <50 case reported in the literature. The full spectrum of the syndrome is not yet known. Results: Here we report a girl who presented with new onset refractory seizures and an undiagnosed cause of intermittent abdominal distention. She also had syndactyly of her fingers and toes and was found to have prolonged QT. Upon further investigations she was found to have a de novo pathogenic variant in CACNA1C, along with Segmental Ileal Dilatation (SID), and subsequently diagnosed with Timothy syndrome. Conclusion: To our knowledge, the association of Timothy Syndrome with Segmental Ileal Dilatation, was not described before.